Pemanfaatan Air Cucian Surimi Belut Sawah (Monopterus albus) dalam Pembuatan Edible Film - Dewi Shinta; Agus Supriadi; Shanti Dwita Lestari (Universitas Sriwijaya, 2016)
The purpose of this research was to obtain edible film that meet physical and chemical characterictics of Japan Internasional Standard (JIS). This research was conducted from June 2015 to December 2015. This research used the randomized bloc design with one factor, the addition of eel surimi waste water (0 mL, 12 mL, 15 mL dan 18 mL). The observed parameters included chemical (water activity) and physical (thickness, percent of elongation, vapor transmission rate) characterictics. The results showed that there were no significant effects on thickness water activity, vapor transmission rate and percent of elongation. Furthermore, the edible film met Japan Industrial standard (JIS) based on thickness 0.139 to 0.214 mm, vapor transmission rate 3.514 to 7.133 g/m2/jam and the percent of elongation 106.22% to 174.55%.